تعقبات ابن جزي الغرناطي على المفسرين من خلال كتابه التسهيل لعلوم التنزيل - زلاسي, مسعود (جامعة الوادي - University of Eloued, 2023)
تُــعد هذه الدراسة الموسومة بــــ: تعقبات ابن جُزي الغرناطي على المفسرين من خلال كتابه "التسهيل في علوم التنزيل" – عرضــاً ودراسة - من بواكير الدراسات التي عُنيت بإبراز الجانب النقدي التفسيري لإمام أهل الأندلس في زمانه المتوفى بالواقعة الشهيرة بمعركة طريف سنة741ه. كما أن محورها الأساس هو تتبع واستقراء المسائل التي تعقب فيها الإمام غيره من أرباب وأعلام فحول علم التفسير، ثم جمعها في مصنف مفرد مستقل يسهل للباحثين الرجوع إليه والاستفادة منه، وأما عن الغاية القصوى، والهدف الأسمى من وراء هذه الدراسة هو الوقوف على مدى إصابة الإمام في تعقباته لأقوال غيره، ولا يتسنى ذلك إلا بدراستها في ضوء القواعد المعتبرة للوصول إلى خلاصة القول فيها. وقصدا لتحقيق تلك الأهداف المنشودة المذكورة آنفا، ونظر لطبيعة الموضوع المتناول اقتضى منا تقسيمه إلى مقدمة، وثلاث فصول، وخاتمة اشتملت على أهم النتائج، وأبرز التوصيات فأما المقدمة فحتوت على المحاور التالية: الإشكالية، والأهداف، وأسباب اختيار الموضوع، والدراسات السابقة، والصعوبات، ومنهج الدراسة، وخطة البحث. وأما الفصل الأول فانطوى تحته ثلاث مباحث، فالأول تطرقنا فيه لبيان عصر الإمام ابن جزي، وذكر أهم جوانب سيرته الذاتية، والعلمية، بدأ باسم والنشأة، والمولد، وانتهاء بالوفاة والآثار العلمية. والثاني: عرفنا فيه بكتاب التسهيل لعلوم التنزيل حيث قمنا بإعداد نبذة حوله، وذلك بتوثيق نسبة الكتاب، وبيان منهج مؤلفه، وذكر أهم مميزاته، وأشهر المصادر المعتمدة في تحريره، كما ذكرنا أيضا بعض ما الملاحظات والمآخذ عليه. والأخير: تناولنا فيه مفهوم التعقب، ونشأته وفوائده، كما عرجنا فيه على منهج الإمام ابن جزي في التعقب، وأبرز الصيغ التي عبر بها عنه. وأما الفصل الثاني فيمثل هو والفصل الأخير الجانب التطبيقي للدراسة، وقد احتوى على مبحثان، خصصنا الأول منه لدراسة التعقبات المتعلقة بالتفسير وعلومه، بينما تناولنا في الثاني: دراسة التعقبات المتعلقة بعلوم القرآن، وقد جاءت متنوعة لتشمل أسباب النزول، والناسخ والمنسوخ وغيرهما. وأما الفصل الأخير: فقد خصصناه لدراسة التعقبات المتعلقة بالمسائل اللغوية والشرعية، وقد اشتمل على مبحثان، وانصب الكلام في المبحث الأول على دراسة التعقبات المتعلقة بالمسائل اللغوية، بينما انصب القول في المبحث الثاني على دراسة التعقبات المتعلقة بالعلوم الشرعية، وقد كان لمسائل الفقه النصيب الأوفر من ذلك، ولا غرابة فإن ابن جزي كما لا يخفى إمام الفقه وأستاذه ومحرره المسائل والتصانيف البديعة والمفيدة في حياضه، ومن تأمل كتابه القوانين الفقهية تجلى له ذلك. وأما الخاتمة فتوصلنا فيها إلى النتائج التالية وهي كالآتي: أن الإمام ابن جزي إمام موسوعي متبحر متقن لعلوم شتى كاللغة والتفسير، والأصول، والقراءات، وأما علم الفقه فلا يختلف اثنان أنه من أعيانه وأئمته، بل جزم بعض من ترجم له أنه شارف على درجة الاجتهاد فيه. أن الإمام ابن جزي قد تنوعت صيغ تعقباته لتشمل الصريحة كوصف القول بالبعد، أو الخطأ أو الفساد، أو البطلان، وغير الصريحة كوصف القول بأن فيه فك لنظم ونحو ذلك. أن الإمام ابن جزي من خلال تعقبه لأقوال غيره، كان متحل بأدب النقد العلمي الرصين، البعيد عن اللّمز والرمي للذوات والأشخاص بالعبارات والألفاظ القبيحة والمستهجنة. أن الإمام ابن جزي قد وفق للصواب في أغلب المسائل التي تعقب فيها غيره. أن الإمام ابن جزي قد حاكى وقلد بعض الأئمة في تعقباته التي أوردها في ثنايا تفسيره، ومن أبرز أولئك الإمام الرازي، وابن عطية، وابن العربي رحمة الله على الجميع. وأخيرا لا يفوتني أن أذيل هذا الملخص بذكر جملة من التوصيات بَدَا لي أنها جوانب مُغْفَلَة تحتاج إلى بحث ودراسة وهي كالآتي: أثر السياق في الترجيح عند الإمام ابن جزي من خلال كتابه التسهيل. القواعد التفسيرية عند الإمام ابن جزي من خلال كتابه التسهيل. قواعد الترجيح وتطبيقاته عند الإمام ابن جزي من خلال كتابه التسهيل -مرجع الضمير أنموذجا- والحمد لله في البدأ والختام، وصلى الله وسلم على سيد وَلَدِ عدنان وعلى آله وأصحابه والتابعين لهم بإحسان، وأسأل الله الكريم أن يجعل هذا العمل صالحا ولوجه خالصا، وأن ينفعنا بما علمنا وأن يزيدا علما إنه ولي ذلك والقادر عليه، آمين، وآخر دعوانا أن الحمد لله رب العالمين. This study, tagged with: Ibn Juzy Al-Gharnati’s tracks on the exegetes through his book “Al-Tassil fi Ulum Al-Tanzil” - a presentation and study - is considered one of the early studies that aimed to highlight the critical and explanatory aspect of the imam of the people of Andalusia in his time who died in the famous incident of the Battle of Tarif in the year 741 AH. Its main focus is to follow and extrapolate the issues in which the imam followed other lords and scholars about the science of interpretation, and then collected them in a single independent work that is easy for researchers to refer to and benefit from. In his follow-up to the sayings of others, and this is only possible by studying them in the light of the considered rules to reach a conclusion about them. In order to achieve those aforementioned desired goals, and given the nature of the subject matter, we had to divide it into an introduction, three chapters, and a conclusion that included the most important results and the most prominent recommendations. As for the introduction, it contained the following topics: the problem, objectives, reasons for choosing the topic, previous studies, difficulties, study method, and research plan. As for the first chapter, three sections were covered under it. In the first, we discussed the era of Imam Ibn Juzay, and mentioned the most important aspects of his biography and science, starting with his name, his upbringing, his birth, and ending with his death and scientific effects. The second: We knew in it the book “Al-Tashil for the Science of Downloading” where we prepared a brief about it, by documenting the percentage of the book, explaining the method of its author, and mentioning its most important features, and the most famous sources approved in its editing, as we also mentioned some of the observations and objections to it. And the last: we discussed in it the concept of tracing, its origins and its benefits, as we referred to the approach of Imam Ibn Juzy in tracing, and the most prominent formulas by which he expressed it. As for the second chapter, it and the last chapter represent the practical aspect of the study, and it contained two sections, the first of which we devoted to studying the traces related to interpretation and its sciences, while in the second we dealt with the study of the traces related to the sciences of the Qur’an. As for the last chapter: we have devoted it to the study of the traces related to linguistic and legal issues, and it included two sections. That, and it is not surprising that Ibn Juzay as the imam of jurisprudence, professor and editor of the issues and classifications wonderful and useful in his life, is not hidden, and whoever contemplates his book jurisprudence laws became clear to him. As for the conclusion, we reached the following conclusions: That Imam Ibn Juzay is a well-versed encyclopedic imam who is well-versed in various sciences such as language, interpretation, principles, and readings, and as for the science of jurisprudence, no two disagree that he is one of his notables and imams. That Imam Ibn Juzay has varied formulas of his tactics to include the explicit, such as describing the saying with distance, error, corruption, or invalidity, and not explicit, such as describing the statement that there is a decoding of systems and so on. That Imam Ibn Juzay, by following the sayings of others, was imbued with the literature of sober scientific criticism, far from blaming and slandering subjects and persons with ugly and reprehensible phrases and words. That Imam Ibn Juzay was correct in most of the issues in which he followed others. That Imam Ibn Juzay imitated and imitated some of the imams in his commentaries that he mentioned in the folds of his interpretation, and among the most prominent of those are Imam Al-Razi, Ibn Attia, and Ibn Al-Arabi, may God have mercy on everyone. Finally, I do not fail to append this summary by mentioning a number of recommendations that seemed to me to be overlooked aspects that need research and study, and they are as follows: The impact of context on the weighting of Imam Ibn Juzy through his book Al-Tas’eel. The Exegetical Rules of Imam Ibn Juzy through his book Al-Tas’eel. The rules of weighting and its applications according to Imam Ibn Juzy through his book Al-Tas’eel - reference of the conscience as a model - Praise be to God at the beginning and at the end, and may God’s prayers and peace be upon the master of the son of Adnan, his family, his companions and those who follow them in goodness. God, Lord of the worlds
عرضا ودراسة
أطروحة دكتوراه تخصص كتاب وسنة في العلوم الإجتماعية و الإنسانية
Keywords: التعقبات، ابن جزي الغرناطي، المفسرين، "التسهيل لعلوم التنزيل"; Tracks,Ibn Djouzai Algharnati, interpreters, "Al-tashil Li Ouloum Attanzil"